A structural equation model-II for work-life balance of IT professionals in Chennai - Banu, Rashida (Serbian Journal of Management, 2016)
The study developed and tested a model of work life balance of IT professionals employing structural equation modeling (SEM) to analyze the relationship between work place support(WPS) and work interference with personal life(WIPL), personal life interference with work(PLIW), satisfaction with work-life balance(SWLB) and improved effectiveness at work(IEW). The model fit the data well and hypotheses are generally supported. WPS and SWLB are negatively related to WIPL and PLIW. However, there is a positive relationship between SWLB and IEW.